MARINATION TIME AND CONCENTRATION OF GALANGAL (Languatis galanga) IN MAINTAIN THE QUALITY OF PHYSICAL AND CHEMISTRY CHICKEN MEAT - Halimah, Nur; Maharani, Nadia; Pristiwaningsih, Estin Roso (Jurnal Pangan dan Agroindustri, 2024)
Chicken meat is a food that is easily damaged, so preservation was required to maintain the quality of the meat both physically, chemically, and microbiologically. One way is to use galangal, which contains phenols, flavonoids, and terpenoid compounds, which reduce microbial activity and inhibit the chemical activity of meat. The research aimed to determine the effect of curing time and galangal concentration on chicken meat's physical and chemical quality. The research method used a 2-factor Completely Randomized Design. The results showed no interaction (p>0.01) between curing time and galangal concentration. The length of curing from 0-4 days has a significantly different effect (p<0.01) on chicken meat's physical and chemical quality. The longer the meat is curing, the quality decreases. Galangal, 10-20% concentration, did not affect chicken meat quality (p>0.01). It means that galangal can maintain the physical and chemical quality of chicken meat.